Guarantees for the Protection of the International legal Status of the Kurdistan Region - Iraq in Light of the Principles and Resolutions of the United Nations - شيركو عبدالكريم بابان بريار; سعدون غريب الجباری هه‌لمه‌ت (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
After the formation of the Kurdistan Region - Iraq, the Parliament of the Kurdistan Region issued legislation distinct from Iraqi laws and more respectful of human rights issues, and all of this allowed the region to participate effectively in the universal periodic review processes, including the submission of national reports and the representative of the Kurdistan Region giving his speech in those processes, and all of this is considered An important development to ensure the international legal status of the region. The Kurdistan Region is the only region in all federal states that took the time to talk about its human rights record independent of the federal state. A speech on the subject of the universal periodic review, that giving a role, even if restricted to the federal region, is considered a development for the Kurdistan Region and international law. The Kurdistan Region-Iraq contributed effectively In a war against terrorism, based on the principle of legitimate defense and in response to Security Council resolutions regarding what terrorism, especially ISIS, poses as a threat to international peace and security.